German MPs' outside jobs and their repercussions on parliamentary effort - Felix Arnold (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
It is a longstanding debate whether members of parliament (MPs) should be allowed to follow sideline jobs in addition to their mandate. Critics claim that politicians already face binding time constraints and that moonlighting might lead to a neglect of inner-parliamentary duties. The purpose of this study is therefore to investigate whether politicians with more sideline jobs show less effort inside parliament. To address this question, I collected novel data on German members of parliament from 2009-2013. Using a selection on observables approach that controls for legislator ability, I find that higher outside earnings are associated with a significantly lower attendance rate as well as fewer speeches, oral contributions, interpellations and group initiatives. These results are robust to a variety of tests. My findings suggest that time caps on moonlighting along with stricter disclosure rules for outside activities might be necessary.
Keywords: D72; D73; J22; 330; Outside Earnings; Parliamentary Effort; Moonlighting Politicians; German Bundestag